MAN AND HIS RELATIONSHIP IN THE DIALOGUE WITH COMMUNITY IN THE ANALYSIS OF GRAMSCI AND VOLOSHINOV - Sandra Dugo; Wander A. Camargo (Travessias, 2012)
This proposal for a comparative reading of Antonio Gramsci and Valentin Voloshinov suggests the reflection on the philosophy of their language. For the Italian philosopher a function of the intellectual in society requires use appropriate language through the use of the word. On the other hand, proposes a Voloshinov theory of language based on the analysis of the word. The goal is to understand the relationship between theories of them, following the line of Marxist thought of their philosophers.